Kajian Keselamatan Lalu Lintas Pada Daerah Rawan Kecelakaan Di Ruas Jalan Palbapang - Samas: Traffic Safety Study In Accident Prone Areas On The Palbapang - Samas Road Section - Raafi Widyaputra Yulianyahya (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study examines traffic safety in areas that are often hit by accidents on the Palbapang - Samas Road Section. This investigation began with the high rate of traffic accidents that endanger the safety of people crossing this road. The research methods used include analyzing the existing literature, conducting direct observations, and gathering key information through surveys and conversations with community members to accurately capture the true situation. Additional information was obtained from relevant organizations, such as the Department of Transportation and local law enforcement, to refine the findings. The results showed that the main reasons for accidents included road design that did not meet standards and the actions of drivers who were not in a traffic order, including excessive speed and ignoring road signs. Many locations known as high-risk zones demand immediate action from local government officials. The conclusion emphasizes the need to improve infrastructure by adding more traffic signs, improving road markings, ensuring adequate lighting, and promoting public awareness initiatives to foster a culture of responsible driving that can significantly lower accident rates.